10-20-2015, 12:53 PM

Hello,

I have two equations.

E1: S=(IP(X/L)*IP(Y/M)+IP(X/M)*IP(Y/L)+ABS(IP(X/L)*IP(Y/M)-IP(X/M)*IP(Y/L)))*0.5

E2:C=IP(X/L)*IP(Y/(2*M-2) )+IP(X/(2*M-2))*IP(Y/L)+ABS(IP(X/L)*IP(Y/(2*M-2))-IP(X/(2*M-2))*IP(Y/L))

When I solve them one by one, the answer is correct:

[attachment=2679]

[attachment=2680]

But, if I solve them at the same time, the answer of E2 is not correct.

[attachment=2681]

Is it a bug?

[attachment=2684]

21-10-2015 attachment updated

Updated on 22-10-2015

I modify the equations to as follows. They have the same problem.

E1:C=IP(X/(2*M-2))*IP(Y/L)*2

E2:B=A

If solve E1 and E2 at the same time, the answer or E1 is not correct.

I have two equations.

E1: S=(IP(X/L)*IP(Y/M)+IP(X/M)*IP(Y/L)+ABS(IP(X/L)*IP(Y/M)-IP(X/M)*IP(Y/L)))*0.5

E2:C=IP(X/L)*IP(Y/(2*M-2) )+IP(X/(2*M-2))*IP(Y/L)+ABS(IP(X/L)*IP(Y/(2*M-2))-IP(X/(2*M-2))*IP(Y/L))

When I solve them one by one, the answer is correct:

[attachment=2679]

[attachment=2680]

But, if I solve them at the same time, the answer of E2 is not correct.

[attachment=2681]

Is it a bug?

[attachment=2684]

21-10-2015 attachment updated

Updated on 22-10-2015

I modify the equations to as follows. They have the same problem.

E1:C=IP(X/(2*M-2))*IP(Y/L)*2

E2:B=A

If solve E1 and E2 at the same time, the answer or E1 is not correct.